(2x-3) (3x + 1) = 0
2x(3x + 1)-3(3x + 1) = 0 taking common from first two terms and last two terms
(2x-3)(3x + 1) = 0
(2x-3) = 0 or (3x + 1) = 0
x = 3/2 or x = (-1)/3
Roots of equation are 3/2, (-1)/3
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation